Theoretical potential for endometrial cancer prevention through primary risk factor modification: Estimates from the EPIC cohort. Issue 5 (18th February 2020) - Fortner, Renée T.; Hüsing, Anika; Dossus, Laure; Tjønneland, Anne; Overvad, Kim; Dahm, Christina C.; Arveux, Patrick; Fournier, Agnès; Kvaskoff, Marina; Schulze, Matthias B.; Bergmann, Manuela; Trichopoulou, Antonia; et al.
Abstract : Endometrial cancer (EC) incidence rates vary 10‐fold worldwide, in part due to variation in EC risk factor profiles. Using an EC risk model previously developed in the European EPIC cohort, we evaluated the prevention potential of modified EC risk factor patterns and whether differences in EC incidence between a European population and low‐risk countries can be explained by differences in these patterns. Predicted EC incidence rates were estimated over 10 years of follow‐up for the cohort before and after modifying risk factor profiles. Risk factors considered were: body mass index (BMI, kg/m 2 ), use of postmenopausal hormone therapy (HT) and oral contraceptives (OC) (potentially modifiable); and, parity, ages at first birth, menarche and menopause (environmentally conditioned, but not readily modifiable). Modeled alterations in BMI (to all ≤23 kg/m 2 ) and HT use (to all non‐HT users) profiles resulted in a 30% reduction in predicted EC incidence rates; individually, longer duration of OC use (to all ≥10 years) resulted in a 42.5% reduction. Modeled changes in not readily modifiable exposures (i.e., those not contributing to prevention potential) resulted in ≤24.6% reduction in predicted EC incidence. Women in the lowest decile of a risk score based on the evaluated exposures had risk similar to a low risk countries; however, this was driven by relatively long use of OCs (median = 23 years). Our findings support avoidance of overweight BMI and of HT use as prevention strategies for EC in a European population; OC use must be considered in the context of benefits and risks. Abstract : What's new? Endometrial cancer rates vary considerably around the world, with incidence rates higher in Europe and North America than in parts of Asia and Africa. Here, the authors investigated how much of the risk disparity arises from modifiable factors, and how much modifying these factors could reduce cancer incidence. The 10% of European women with lowest risk had similar incidence to women in low‐risk countries, they found. Their model predicted that in European women, maintaining BMI below 23 kg/m 2 and avoiding postmenopausal hormone use could reduce risk by 30%. Long‐term use of oral contraceptives could reduce risk by 42.5%.